Management of Pt1 tumours removed by endoscopy during colorectal cancer screening: Outcome and treatment quality indicators. Issue 12 (December 2018) - Senore, Carlo; Giovo, Ilaria; Ribaldone, Davide Giuseppe; Ciancio, Alessia; Cassoni, Paola; Arrigoni, Arrigo; Fracchia, Mario; Silvani, Marco; Segnan, Nereo; Saracco, Giorgio Maria
Abstract: Introduction: Limited information is available about outcomes of patients with malignant adenomas endoscopically resected at screening. The aim of the study was to evaluate diagnostic and therapeutic quality indicators and to correlate them with clinical and surgical outcomes. Materials and methods: We reviewed endoscopic and histology characteristics of all pT1 tumours endoscopically removed at the time of colonoscopy assessment in subjects with a positive screening test result in the context of a population-based program. Results: 392 pT1 tumours were completely removed by endoscopy (en-bloc = 86.7%, piecemeal = 13.3%) and the histology report was considered complete in 83.2% of cases. Treatment was limited to endoscopic excision for 120 patients (30.7%, Group 1), 272 (69.3%, Group 2) underwent radicalisation surgery. In patients who had at least 1 lymph node examined, the rate of nodal involvement was 5.4% (13/239); no metastatic node was found in the 21 (27.6%) out of 76 patients with low-risk adenomas, who underwent surgery. Conclusion: Risk of nodal involvement in colorectal pT1 tumours is well predicted by known histologic features also in a screening setting, although it was lower than among patients from clinical series. Surgical overtreatment is still significantly present and there is ample room for improvement regarding diagnostic and therapeutic flow-chart.